2021
DOI: 10.1038/s41598-021-81948-4
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative models disentangle drivers of fruit production variability of an economically and ecologically important long-lived Amazonian tree

Abstract: Trees in the upper canopy contribute disproportionately to forest ecosystem productivity. The large, canopy-emergent Bertholletia excelsa also supports a multimillion-dollar commodity crop (Brazil nut), harvested almost exclusively from Amazonian forests. B. excelsa fruit production, however is extremely variable within populations and years, destabilizing local harvester livelihoods and the extractive economy. To understand this variability, data were collected in Acre, Brazil over 10 years at two sites with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 44 publications
5
18
0
1
Order By: Relevance
“…They found that trees > 40 cm in DBH had a 50% probability of being reproductive, whereas we found that the trees of similar size had a 63% probability of being reproductive. This variation is likely caused by differences in sample size and location of these studies and shows that Bertholletia reproduction capacity may vary within a region [55]. Despite the positive effect of Amazon nut harvesting intensity on fruit production and upon accounting for the positive relationship between tree size and the percentage of unharvested fruits, Amazon nut harvesting intensity decreased the overall Bertholletia fecundity rate.…”
Section: Discussionmentioning
confidence: 87%
“…They found that trees > 40 cm in DBH had a 50% probability of being reproductive, whereas we found that the trees of similar size had a 63% probability of being reproductive. This variation is likely caused by differences in sample size and location of these studies and shows that Bertholletia reproduction capacity may vary within a region [55]. Despite the positive effect of Amazon nut harvesting intensity on fruit production and upon accounting for the positive relationship between tree size and the percentage of unharvested fruits, Amazon nut harvesting intensity decreased the overall Bertholletia fecundity rate.…”
Section: Discussionmentioning
confidence: 87%
“…Extreme weather events have become more frequent in southwestern Amazon and the years 2005, 2010, and 2016 registered the most severe droughts, causing forest fires in thousands of hectares, increasing air pollution and causing significant economic losses (Oliveira et al, 2017). Staudhammer et al (2021) state that the variation in Brazil nut fruit production in Acre State has also been affected by aspects related to soil characteristics, vegetative competition, higher temperatures in the dry season, and pressure deficit of water vapor in the air.…”
Section: Sustainability Indicators Of the Environmental Dimensionmentioning
confidence: 99%
“…It is therefore those households whose colocações happen to have most Brazil nut trees that are, in principle, in a more favourable economic position, compared to those with no or limited access [17]. The effects of such unequal access are further enhanced by the high variability in Brazil nut yields both in time (annually) and space, with some trees regularly producing little or no fruit and others producing more reliable, abundant yields [18]. At the same time however, as we discuss below, some of the social institutions derived from the rubber economy help alleviate some of the consequences of unequal access and distribution through sharing of access and resources.…”
Section: Introductionmentioning
confidence: 99%